Human Rights Violation of Transgender People: A Critical Analysis on Bangladesh Perspective - Mitra, Puja (Kathmandu School of Law Review, 2018)
Transgender people are discriminated based on their gender identity, especially, in the societies of South Asian countries. The legal recognition of this ‘third sex’ had to wait long in countries like India, Pakistan, Nepal and Bangladesh. The human rights of these people are being violated in every sector although having been recognized as ‘citizens’ by their respective governments. Many countries have already started to let them get involved in different social and economic activities. In 2013, the Bangladesh government declared the status of the third gender to the transgender people of its territory. This recognition was aimed to protect all the human rights of the third gender enabling them to identify their gender as ‘Hijra’ in all government documents and passport. Section 27 of the Constitution of Bangladesh states that ‘All the citizens are equal before the law and are entitled to equal protection of law’. But the legal protection of the human rights of the newly recognized third gender is questionable till now. The Prevention of Oppression against Women and Children Act, 2000 describes the rights of only women and children. In Bangladesh, the transgender people are becoming rape victims everywhere but unlike women and children, their rape cases never get filed as the police officers do not even believe that anyone can rape these third genders. This social taboo and negligence are costing the sexual minorities their human rights like legal protection. Therefore, it has become important to address this issue to create social awareness which might induce the urgency to practice equal laws for every gender identity. In this paper, a critical analysis of the human rights of Bangladeshi transgendered people has been performed. Finally, the human rights condition of transgender people of Nepal and India is also discussed. DOI: https://doi.org/10.46985/jms.v6i2.212